AUTHENTIC ASSESSMENT IN HOLISTIC LEARNING: ITS IMPLICATIONS FOR STRENGTHENING THE PANCA JIWA CHARACTER IN ISLAMIC BOARDING SCHOOLS - Dwi Istiyani; Mustopa Mustopa; Nasikhin Nasikhin; Zulaikhah Zulaikhah; Agus Sutiyono (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
This study analyzes the implementation of authentic assessment in holistic learning and its impact on strengthening five student characters in a semi-modern Islamic boarding school. Using a qualitative case study at Pabelan Islamic Boarding School in Magelang, data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that authentic assessment not only assesses learning outcomes but also the process of character formation through the integration of cognitive, affective, and psychomotor aspects. Its implementation is carried out through project-based, performance-based, and portfolio-based assessments integrated into the students' daily activities. This approach has been proven to strengthen the main character values of sincerity, simplicity, independence, Islamic brotherhood, and freedom through reflective, participatory, and contextual learning. In addition, social interactions within the Islamic boarding school environment also strengthen the internalization of values on an ongoing basis. However, challenges exist in the form of limited teacher competency, administrative burdens, and student-to-student ratios. Therefore, ongoing training and strengthening of the evaluation system are needed to optimize the implementation of authentic assessment in holistic character education.